Agile management and organizational flexibility and their role in achieving high performance - Jasim, Jasim Saad (Universitas Tanjungpura, 2025)
Background. This research investigates the relationship between the application of Agile management principles and the adoption of organizational flexibility in sports clubs, highlighting their essential role in enhancing performance levels. Objectives. The main objective is to explore how Agile management and organizational flexibility contribute to the performance of football club administrative bodies in Dhi Qar Governorate. Methods. The study employed a descriptive and analytical approach. A total of 133 questionnaires were distributed to selected members of the administrative bodies of football clubs in Dhi Qar Governorate using a purposive sampling method. Data were collected through a structured questionnaire, and statistical analysis was conducted to determine the levels of Agile management implementation, organizational flexibility, and performance impact. Results. Findings revealed that respondents showed an average level of awareness and application of Agile management principles within their clubs. The influence of both Agile management and organizational flexibility on administrative performance was modest. However, the data indicate a positive, albeit limited, correlation between these variables. Conclusion. The study concludes that while Agile management and organizational flexibility are present to a moderate extent in the administrative practices of football clubs, their full potential in improving performance remains underutilized. The research recommends greater commitment by club administrations to Agile management principles to better meet performance and quality standards.